2015
DOI: 10.1007/s11606-015-3355-x
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Multifaceted Trial to Improve Hypertension Control in Primary Care: Why Did it Work?

Abstract: BACKGROUND: It is important to understand which components of successful multifaceted interventions are responsible for study outcomes, since some components may be more important contributors to the intervention effect than others. OBJECTIVE: We conducted a mediation analysis to determine which of seven factors had the greatest effect on change in systolic blood pressure (BP) after 6 months in a trial to improve hypertension control. DESIGN: The study was a preplanned secondary analysis of a cluster-randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 26 publications
1
48
1
2
Order By: Relevance
“…The study design and methods are described in detail in the Supplement and in previous reports, 15,18,19,20,21,22 and recruitment, enrollment, and follow-up of the study cohort are shown in Figure 1. Briefly, we used electronic data to identify individuals and mail recruitment letters between March 2009 and April 2011 to 14 492 adult patients who had BP of 140/90 mm Hg or higher at the 2 most recent primary care encounters in the previous year.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and methods are described in detail in the Supplement and in previous reports, 15,18,19,20,21,22 and recruitment, enrollment, and follow-up of the study cohort are shown in Figure 1. Briefly, we used electronic data to identify individuals and mail recruitment letters between March 2009 and April 2011 to 14 492 adult patients who had BP of 140/90 mm Hg or higher at the 2 most recent primary care encounters in the previous year.…”
Section: Methodsmentioning
confidence: 99%
“…Especially, studies with a long follow-up have shown effect on blood pressure, like the HyperLink study using a multifaceted approach in a cluster randomized design. 18 After 12 months they found a 11.3-mm Hg systolic difference in blood pressure reduction. After 6 months another primary-care study found a mean difference in daytime ABPM of 4.3 mm Hg systolic and 2.3 mm Hg diastolic.…”
Section: Short-term Tbpm In Hypertensive Patients N Hoffmann-petersenmentioning
confidence: 95%
“…Paul, MN, metropolitan area that is part of an integrated health system. Study recruitment, enrolment and outcomes from the HyperLink trial are described previously . In the HyperLink trial, 2020 patients were screened and 450 were identified as eligible and volunteered to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Self‐reported medication adherence improved more in the TI group compared with UC; however, it was not a significant mediator of the greater blood pressure lowering in the TI group. One potential explanation is the high rate of medication adherence at baseline may have left little room for further improvement . Another possibility is that measurement error inherent in self‐reported adherence made it difficult to discern any improvement.…”
Section: What Is Known and Objectivementioning
confidence: 99%